The American University of Beirut, its founding idea and the system of appointing its presidents and professors (Journal of the College of Basic Education, 2023)
This research consists of two chapters, the first discussing the establishment of the American University in Beirut in 1866 and the role of American missionaries and their efforts to obtain financial and moral support from senior businessmen in Washington and Britain.As for the second research, it dealt with the system of appointing university presidents and professors, which was carried out according to several conditions, perhaps the most prominent of which is competence and scientific production. It is remarkable that most of the university presidents completed their university studies in theology. In addition to the fact that university presidents remained in office for a long time, the matter Which enabled them to establish solid university rules and traditions.